Respiratory bacterial and viral pathogen spectrum among influenza-positive and influenza-negative patients - Jing Shi; Shi Han; Yating Zhang; Xiaohua Lu; Yunxia Gan; Narenqimuge Tong; Lu Ma; Hang Zhuan; Ying Dai; Yaqi Ji; Guoming Li; Dan Chen; et al. (BMC Infectious Diseases)
Abstract Background Respiratory tract infections are a significant burden on public health worldwide, with influenza being a prominent viral infection. Although influenza is known to predispose individuals to secondary bacterial infections, the precise spectrum of respiratory pathogens in influenza-positive and negative-patients remains unclear. This study aims to gain insights into the pathogenesis, epidemiology, and clinical implications of co-infections, facilitating the development of preventive and targeted interventions. Methods A total of 1,596 oropharyngeal swabs from influenza-like cases were collected from 2021 to 2023 and analyzed using real-time PCR. These samples tested for 9 different respiratory bacteria, such as Streptococcus pneumonia and Neisseria meningitides, and 8 respiratory viruses, including human influenza virus and human metapneumovirus. Results This study collected samples from 403 influenza-positive patients and 1,193 influenza-negative patients, among which bacterial and viral pathogens were detected. The gender distribution among the influenza-positive and influenza-negative patients was approximately equal with males slightly outnumbering females. The age range of the participants varied from one month to 97 years old. Co-infection of influenza virus with other common respiratory bacterial and viral pathogens was identified and evaluated highly relevant for an accurate understanding of the disease's overall burden. Specifically, Streptococcus pneumoniae and Haemophilus influenzae were significantly more prevalent in influenza-positive patients (30.77% and 33.00%, respectively) compared to influenza-negative patients (22.21% and 22.46%, respectively). Conversely, Human parainfluenza viruses and Human rhinoviruses were more prevalent in influenza-negative patients (4.27% and 5.62%, respectively) compared to influenza-positive patients (0.74% and 1.49%, respectively). A total of 995 cases (62.34%) tested positive for nucleic acid, with 254 cases of single-virus infections, 297 cases of single-bacterial infections, and 444 cases of mixed infections. The most common co-infection pattern was H. influenzae and influenza virus, accounting for 133 cases (29.95% of mixed infections). Conclusion Our study highlights the high prevalence of co-infections in respiratory infections, with significant differences in pathogen distribution between influenza-positive and influenza-negative patients. Influenza-positive patients had higher rates of S. pneumoniae and H. influenzae infections, while influenza-negative patients had higher rates of Human parainfluenza viruses and Human rhinoviruses. These findings underscore the importance of comprehensive pathogen testing for accurate diagnosis and tailored treatment strategies. Trial registration The samples for this study were obtained from the influenza surveillance network of Hubei Province. The information contained in the study does not pose any ethical or privacy risks to the sample providers. The need for ethics approval for this study was waived by the statement from the research ethics board of the Hubei Provincial Center for Disease Control and Prevention. Additionally, the requirement of obtaining informed consent to participate was also waived.